Plan de negocios para la creación de una empresa de corretaje inmobiliaria en la ciudad de Quevedo año 2014. - Briones Macías, Paola Nayce (2015)
In today's competitive environment, the formation of a real estate company with innovative and personalized customer services and demand that these operations requires structuring a business plan containing a set of planned activities to achieve goals proposals for the success of the consultant; proactively designed it with vision and growth. In the present investigation, this business will be performed in order to identify opportunities in the real estate market and create a business of real estate services with the decision to devote financial resources, time and effort in developing a novel idea of real estate and give the user of the services sector, the largest quantity and quality of information through a management professional judgment. To design field study with descriptive level contemplate framed within the type of research…..